Factors relating to the low interest in intrauterine device contraceptive methods - Fatimatuzzahra, Aza; Kurniawati, Dini; Rahmawati, Ira (Universitas Airlangga, 2023)
Introduction: A contraceptive with a modern design, the device is implanted in the uterine cavity to prevent fertility and the egg from implanting in the uterus, called intrauterine devices (IUD). It's emphasizing maternal mortality and controlling the rate of population growth causing. This study aimed to determine the factors associated with the low interest in the IUD contraceptive method in Jambesari District, Bondowoso Regency. Methods: This study used a descriptive quantitative approach with random sampling for cross-sectional analysis. Primary data were gathered through questionnaires and analyzed using univariate and bivariate methods supplemented by secondary data. The study focused on 6,677 mothers using family planning, with a 99-participant sample determined by the Slovin formula. The analysis involved the Chi-square test at a 95% confidence level based on categorical and ordinal data. Results: There is a relationship between the level of knowledge of acceptors, education level, and attitude towards the low number of IUD users in Jambesari Bondowoso District (p=0.00). Conclusion: Based on the research results that have been described, it can be concluded that in Jambesari District, there are 7 factors, 3 factors (knowledge, education, attitude) related to poor knowledge due to low education, resulting in acceptors having a bad attitude or agreeing to IUD contraception. Health workers should be more active in providing counselling and education. Keywords: childbearing age; influenced factor; intrauterine devices (IUD)